Rancang Bangun Alat Ukur Kadar Protein Pada Makanan Pokok Berbasis Iot Dengan Kendali BOT Telegram - Billy Hendrik; Ruri Hartika Zain; Afifah Syahidah Nahda (Jurnal Ilmu Komputer dan Informatika | E-ISSN : 3063-9026, 2026)
Protein is one of the macronutrients that is very important and essential for the human body. This substance functions in various biological processes, including as a builder of muscle tissue, skin, enzymes, hormones, and the body's immune system. Although important, monitoring daily protein consumption is often not carried out accurately by the general public. Most people only rely on rough estimates based on the type of food consumed, or nutritional information printed on the packaging label. This is a challenge, especially for staple foods or home-made foods that do not have nutritional labels. One technology that supports the development of this system is a load cell, which is able to measure the mass or weight of an object precisely and stably. This sensor is widely used in digital scales and industrial systems. In the context of protein measurement, the weight of a food ingredient can be converted to an estimate of its protein constent, based on the average protein content data of each type of food that has been determined. With the help of a microcontroller such as Arduino, ESP32, or other types, this system can regulate the logic flow of the tool's operation, calculate protein levels based on input from the load sensor, and display the measurement results to the user via an output device such as a 20x4 LCD. In addition, the use of infrared (IR) sensors as object presence detectors allows the system to recognize when food has been placed on the device, so that the measurement process can be carried out automatically and responsively.